Wind generated ocean waves - Young, I. R. (Elsevier, 2020)
The goals of wind wave research are relatively well defined: to be able to predict the wind wave field and its effect on the environment. That environment could be natural (beaches, the atmosphere etc.) or imposed by human endeavour (ports, harbours, coastal settlements etc.). Although the goals are similar, the specific requirements of these various fields differ considerably. This book attempts to summarise the current state of this knowledge and to place this understanding into a common frame work. It attempts to take a balanced approach between the pragmatic engineering view of requiring a.